STRESS COPING AS A PSYCHOLOGICAL FACTOR FOR CHRONIFICATION OF LOW BACK PAIN - Millere, Anna; Kalnberza-Ribule, Zaiga; Nulle, Anda; Deklava, Liana; Millere, Inga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Stress is a part of our everyday life and it plays an important role in causing various diseases including low back pain and vice versa chronic pain is a stressor that is challenging stress system of the human body. Purpose of the study is to examine stress coping among patients with low back pain in rehabilitation practice in Latvia. Demographic questionnaire, Visual analogue scale and “The Ways of Coping scale” were used. Results. Almost all stress coping strategies scores for patients with low back pain in their first visit are higher than in patients with revisit to Physical Medicine and Rehabilitation doctor and there is statistically significant difference in the use of problem oriented stress coping. Conclusion. This research is meaningful due to the fact it allows to acknowledge and evaluate the spectrum of stress coping ways for patients with low back pain.